Hybrid microwave sintering of Zinc Aluminum Alloy / Maisarah Lutfi - Maisarah, Lutfi (2012)
Commercial Zinc-Aluminum (Zn-Al) alloys commonly manufactured through traditional process of melting and casting. However, the problems with the casting process in producing mass production parts are associated with segregation, machining and maintaining final tolerance. Therefore, this research aims to produce commercial Zn-Al alloys from powder elements, study its sintering behavior through hybrid microwave sintering method and compared with the performance of conventional sintering. The comparative analyses are based on density, porosity, micro hardness, grain size, microstructure and XRD analysis of the sintered samples. In this research, three different compositions of Zn-Al alloys; Zn-8wt.%Al-1wt.%Cu-0.02wt.%Mg (ZA8), Zn-11wt.%Al-1wt.%Cu-0.025wt.%Mg (ZA12) and Zn-27wt.%Al-2wt.%Cu-0.015wt.%Mg (ZA27) are mixed in a planetary ball mill at 100 rpm for 4 hours. Samples are prepared by hydraulic pressing at three compaction loads; 6, 8 and 10 tons. In conventional sintering, the green samples are sintered to sintering temperature; 360°C, the heating and cooling rates were set to 5oC/min and holding time; 30 minutes. A modification of 2.45 GHz domestic microwave oven is implemented into hybrid system by adding insulation box, susceptor and crucibles to sinter the samples at sintering temperature; 360°C and holding time; 10 minutes. Hybrid microwave sintering technique is employed to overcome the problems in pure microwave metal sintering which requires a long warming-up before the compact will start to couple with the microwave. This will increase the risk of plasma formation in the cavity and lead to damage of microwave generator-magnetron. The results shown that hybrid microwave sintering of Zn-Al alloys took considerably shorter processing time, higher density, higher hardness, lower porosity and uniform microstructure compared with conventional sintering. The best compaction load for processing ZA8 and ZA12 alloys were 8 tons meanwhile for ZA27 alloy was 10 tons. ZA8 alloy obtained the highest density compared to ZA12 and ZA27 alloys because of weight percentage of zinc in the compositions. Coefficient of thermal expansion (CTE) is decreased by increasing Al fraction in the all ZA8, ZA12 and ZA27 alloys.